HUBUNGAN WORK FAMILY CONFLICT DENGAN COUPLE BURNOUT PADA WANITA GENERASI Z YANG BEKERJA - Kakana Puan Talensya,; Ratriana Yuliastuti Endang Kusumiati, (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the relationship between Work–Family Conflict and Couple Burnout in married, working Generation Z women. The phenomenon of conflict between work demands and family responsibilities is increasingly experienced by young women in the modern era, which potentially decreases the quality of the marital relationship and emotional well-being. This research used a quantitative approach with a correlational method. The research subjects consisted of 357 married, working Generation Z women, obtained through a purposive sampling technique. The instruments used were the Work–Family Conflict scale (21 items; α = 0.960) and the Couple Burnout scale (18 items; α = 0.967). The normality test results showed that the data was not normally distributed (Kolmogorov–Smirnov p = 0.000), so the analysis was conducted using the non-parametric Spearman correlation. The results showed a very significant positive relationship between Work–Family Conflict and Couple Burnout with a correlation coefficient of ρ = 0.788 and p = 0.000 (p < 0.05). The mean scores for Work–Family Conflict were 44.13 and for Couple Burnout were 54.64, both falling into the moderate category. This indicates that the higher the level of conflict between work and family, the higher the level of emotional exhaustion in the couple's relationship. These findings support the role conflict theory, which explains that work pressure can negatively impact the well-being of the marital relationship. This study emphasizes the importance of maintaining work–life balance and social support for Generation Z women to prevent couple burnout and maintain household harmony.